Evaluating the demand for meat in South Africa: an econometric estimation of short term demand elasticities. Issue 1 (2nd January 2017) - Delport, Marion; Louw, Marlene; Davids, Tracy; Vermeulen, Hester; Meyer, Ferdi
ABSTRACT: The study aims to improve understanding of meat demand in South Africa through the estimation of a Linear Approximation of an Almost Ideal Demand System (LA/AIDS) for the South African meat complex which includes beef, mutton, pork and poultry. As the most widely consumed animal protein, a special focus is placed on poultry, which is disaggregated into two separate product groups, namely IQF portions and other poultry products, providing an improved understanding of demand preferences among different poultry cuts. In light of the changes that have occurred in both global agricultural markets and the South African consumer environment over the past decade, the model is estimated based on monthly data from January 2008 to September 2014, yielding short run elasticities. Expenditure elasticity estimates for IQF portions, other poultry products, pork, mutton and beef were 1.17, 1.24, 0.44, 1.07 and 0.8 respectively and the compensated own-price elasticities were estimated as −0.61, −0.43, −0.72, −0.96 and −0.11 for IQF portions, other poultry products, pork, mutton and beef, respectively. Most of the estimated elasticities conformed to a priori expectations, with the exception of poultry expenditure elasticities, which were higher than expected and in line with luxury goods, rather than normal goods, as the most affordable source of protein. Within the lower income consumer groups, where poultry dominates meat consumption, it was argued that meat in itself is a luxury good, reflected in the elasticities of poultry as the most affordable entry point into the meat market.